Multi-Timepoint Metabolic Fingerprinting of a Post-Episode Period of Hypoglycemia and Ketoacidosis Among Children With Type 1 Diabetes - Małachowska, Beata; Pietrowska, Karolina; Młynarski, Wojciech; Szadkowska, Agnieszka; Krętowski, Adam; Ciborowski, Michał; Fendler, Wojciech (Frontiers in Molecular Biosciences, 2022)
Background: Acute complications of type 1 diabetes mellitus like diabetes ketoacidosis (DKA) and hypoglycemia (HG) are detrimental in the short- and long- term perspective. Restoration of normoglycemia and correction of pH does not mean that all metabolic disturbances caused by HG or DKA are immediately reversed. Aim: To identify serum metabolic changes caused by an episode of DKA and HG, that may indicate on mechanisms contributing to long-term consequences of DKA/HG. Materials and methods: Four groups of children with type 1 diabetes were recruited. The first two study groups included patients after an episode of DKA or HG, respectively. Additionally, two comparative groups were recruited – children with established type 1 diabetes (EDM) and patients with newly diagnosed diabetes without diabetes ketoacidosis (NDM). Serum samples were collected in three group-specific time points (since the hospital admission): HG 0h-12h-48h; DKA or NDM 0h-24h-72h and one random fasting sample from patients with EDM. Two batches of 100 samples each were created: for DKA batch 20x3 DKA patients, 10x3 NDM and 10 EDM; for HG batch: 10x3 HG patients, 25 EDM and 15x3 NDM. All patients within the batches were age- and sex-matched. Metabolic fingerprinting was performed with LC-QTOF-MS. Results: Four metabolites were associated with a DKA episode occurring in the preceding 72 hours: 3 were found higher after DKA episode versus comparative groups: lysophosphatidylcholine (LPC) (18:1), sphingomyelins (SM) (34:0 and d18:0/15:0) and one was found lower– LPC (18:0). Similarly, four metabolites were identified for the HG episode in last 48 hours: 3 were found higher after HG episode versus comparative groups: two lysophosphatidylethanolamines: (LPE) (18:2 and 20:3) and one LPC - (18:2); and one was found lower after HG episode - oxy-phosphatidylocholine (PC O-34:4). Conclusions: We found 8 metabolites which levels may be traced in serum, indicating DKA or HG episode for up to 72h and 48h, respectively. Acute complications of diabetes may cause persistent metabolic disturbances long after pH and glucose levels normalization.